Development of flax/basalt/PA11 bio-composites: optimal formulation and modelling of the quasi-static behaviour - Guerfala, Wassim; Rozycki, Patrick; Binetruy, Christophe (Frontiers in Materials, 2023)
The environmental impact is becoming increasingly important in the automotive industry, pushing OEMs to reduce CO2 emissions through clean engines and weight reduction of structures. Composite materials offer an excellent alternative to standard steels with a considerable weight reduction. Polymer composites remain limited in the automotive industry due to various technical, economic, and environmental constraints. The environmental impact became increasingly critical with new European regulations aiming to reduce CO2 emissions and the carbon footprint during the life cycle automotive structures. The main objective of this research work is to define a new concept for semi-structural automotive parts (hood, door, dashboard…) that can meet the different industrial requirements while reducing their environmental impact. This article presents the results of an experimental study where different designs of natural fibres reinforced PA11 materials are manufactured and compared. The combination of flax and basalt fibers with a bio-based PA11 is analysed to get the best synergistic effect. To do so, three level of hybridisation at the stack, ply and roving scales are compared for different orientations (0°/45°/90°) and quasi-static mechanical tests. The impact of the hybridisation on the quasi-static mechanical behavior is discussed